The protocol for a pilot feasibility trial of Improving Neurodevelopmental ouTcomes After prenatal Cannabinoid in uTero exposure (INTACT) study for a multi-center trial - Jessie R. Maxwell; Leigh-Anne Cioffredi; Maria M. Talavera-Barber; Matthew Henry; Sandra Beauman; Anne Hittson; Meggie McCoy; Laurie Chassereau; Jing Jin; Preetha A. Abraham; Linda Y. Fu; Hengameh Raissy; et al. (PLoS ONE, 2025)
Background Legalization of recreational cannabis use is expanding across the United States, and prenatal cannabis has steadily increased. Evidence suggests that many pregnant individuals use cannabis to relieve symptoms like nausea. Research has demonstrated an association between prenatal cannabinoid exposure and infant deficits in attention, planning, and memory. In other high-risk populations, interventions aimed at increasing parental responsiveness have improved cognitive functioning in the children. This pilot trial aims to utilize a contingent responding training program in birthing parent-infant dyads with prenatal cannabinoid exposure to assess the feasibility of recruitment, completion of the proposed intervention and adherence. Methods This study will enroll post-partum birthing parents who used cannabinoid products during pregnancy at three clinical sites. After consenting and confirming eligibility, birthing parents will be oriented to the online program Play and Learning Strategies (ePALS) by the study team member, after which they will complete asynchronous monthly modules for 12 months that highlight aspects of contingent responding. Study staff at each site will be trained as coaches, meeting monthly with the birthing parent to review and reinforce the areas of focus. The primary objectives of the study will focus on the ability to recruit eligible birthing caregivers with cannabinoid use during pregnancy, the ability to retain participants for the intervention duration as measured through completion of the study session when the child is 12 months of age, and to assess the overall participant adherence of monthly sessions. Discussion As cannabinoid use during pregnancy becomes more prevalent, it is critical that we can provide interventions to optimize infant developmental outcomes. This pilot trial is focused on adapting a proven intervention used in other high-risk populations to determine if it can be applied to this population. If successful, a future trial would focus on the efficacy of this intervention following prenatal cannabinoid exposure. Trial registration Clinicaltrials.gov NCT06423664.